The Role of the Tambakberas Islamic Boarding School in the Jihad Resolution of the Laskar Hizbullah in the “10 November 1945 War” in Surabaya - Muhammad Subhan (Tsaqofah, 2023)
The role and struggle of pesantren cannot be separated from Indonesian history. Behind the Indonesian Revolution war’s success, it turns out that the power of religion (Islam) plays an essential role in it, especially the role of Islamic boarding schools, which always contribute according to the times and conditions. With his desire to defend Indonesia’s homeland, the Ulama directly guided the santri so that the ranks of Laskar Hizbullah were formed. So the purpose of this research is to describe the role and contribution of the Tambakberas Islamic boarding school as the center of the Laskar Hizbullah in Jombang in fighting for and defending Indonesian independence. The method used is the historical method. There are heuristic or collecting sources; a critic or source criticism by looking for certainty of authentic or inauthentic sources; interpretation; and historiography. The results of this study provide information that the Tambakberas Islamic Boarding School, as the center of the Laskar Hizbullah in Jombang, has a role as the foundation for the formation of the Laskar Hizbullah in Jombang. Kiai Wahab Hasbullah, an accomplished leader in building a sense of nationalism in the Tambakberas Islamic Boarding School santri through the song Syubbanul Wathon (Hubbul Wathan), is in the spotlight, the primary place for regeneration training of Jombang Laskar Hizbullah. Spiritual education by Kiai Fattah Hasyim and Kiai Wahib Wahab became the primary movers in the Tambakberas Islamic Boarding School santri movement in the November 10, 1945 war.